Hubungan Kedisiplinan Administrasi Perawat dengan Kualitas Pelayanan di Instalasi Gawat Darurat RSUD Kayu Agung Kabupaten Ogan Komering Ilir: Penelitian - Sunirah; Rini Herdiani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The quality of hospital services is the level of health services that are able to satisfy patients and meet standards, including clinical aspects, efficiency, patient safety, and patient satisfaction with the environment and staff interactions. The aim of this study is to determine the administrative discipline of nurses (Documentation, Implementation of SOP, and Implementation of ASKEP) simultaneously with the quality of service at the Emergency Installation of Kayu Agung Regional Hospital, Ogan Komering Ilir Regency. The design of this research is an analytical survey with a cross-sectional approach. The population in this study was all nurses working in the Emergency Installation of Kayu Agung Regional Hospital, Ogan Komering Ilir Regency, totaling 36 people and the sample of this study was the total of the population. From the entire analysis process that has been carried out, it can be concluded that of the 3 independent variables that are suspected of being related to service quality, it turns out that all of them are proven to be significantly related to service quality, namely documentation, implementation of SOP, and implementation of ASKEP. The Documentation variable after statistical test analysis with Chi-Square obtained p value = 0.000 where the α value (0.05) is greater than the p value (0.000) which means there is a significant relationship between Documentation and service quality, while for the SOP Implementation variable from the statistical test results with Chi-Square obtained p value = 0.002 where the α value (0.05) is greater than the p value (0.002) which means there is a significant relationship between the implementation of SOP and service quality, then for the ASKEP Implementation variable after statistical test analysis obtained p value = 0.005 which means there is a relationship between the Implementation of ASKEP and Quality in the Emergency Installation of Kayu Agung Regional Hospital, Ogan Komering Ilir Regency. Thus, the hypothesis stating that there is a significant relationship is statistically proven. These results are expected to be useful for future researchers to increase knowledge and provide references.